Heart failure and prognosis in patients with infective endocarditis - E. V. Minakov; N. V. Nekrasova; Yu. A. Sobolev; O. N. Choporov (Российский кардиологический журнал)
Infective endocarditis (IE) is still an actual and urgent problem of modern medicine, due to its increasing prevalence and incidence, as well as outcome unpredictability, despite aggressive antibacterial therapy. Mechanisms and patterns of heart failure pathogenesis in IE, its short- and long-term prognosis were studied. In total, 92 cases of sub-acute IE (1996-2003) were analyzed. lethality was as high as 34.7%. Most patients had combined aortal and mitral valve pathology (63%). Prognosis was better in secondary IE and mitral valve pathology. In secondary IE group, two lethality peaks were observed: in first 50 days, and at forth month. There was no significant difference in intracardial hemodynamics among died and non operated IE patients, with the exception of individuals with right heart damage. Therefore, short-term IE prognosis was determined not only by heart failure, in contrast with long-term prognosis.